Determination of Eligibility for Employee Transfers Using the Mabac Algorithm - Allwin M Simarmata; Serfasius Gowasa (Jurnal Mantik, 2021)
Employee transfer is a common activity in an organization. The transfer is intended to position the employee in the right group so that the employee will obtain job satisfaction while also providing maximum performance. The difficulties detected in this study are the large number of employees, which makes it difficult for the management to make decisions in a fast time. To solve the problems identified in this study, the authors are interested in designing the feasibility determination for employee transfers by applying the MABAC method. MABAC stands for Multi-Attributive Border Approximation Area Comparison. MABAC was proposed by Pamucar and Cirovic. The basic concept of the MABAC method is viewed from the basis of the distance function criteria from each alternative which is seen from the prediction area of ??the border. Based on the results of the application of the MABAC algorithm for the employee mutation process involving 60 alternatives with 8 assessment criteria, the decision was obtained that the employee selected for employee transfer was A19.